2016
DOI: 10.21276/aimdr.2016.2.5.pe3
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug - Resistant Acinetobacter Species Infection among Neonates

Abstract: Background: Multidrug resistant Acinetobacter infection has emerged as an important pathogen in neonatal sepsis in the recent years causing morbidity as well as mortality. Methods: Neonates admitted with sepsis in NICU from Jan 2014 to Dec.2014 were retrospectively analysed to find out the incidence, clinical features, antibiotic sensitivity pattern and the risk factors associated with mortality in culture positive Acinetobacter sepsis. Results: Incidence of neonatal sepsis was 11.3% (26/230).Neonatal sepsis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This study showed with gestational age lower than 36 weeks, actinobacteria prevalence was significantly higher in females than males. and this was supported by Keskar et al (15) who revealed that Acinetobacter cases are more common in females, babies under 1500 g and under 30 weeks gestation than non-acinetobacter cases. Acinetobacter cases were less common among males, newborns with a birth weight of more than 1500 g, gestational ages of more than 30 weeks, and normal deliveries, compared to non-Acinetobacter cases.…”
Section: Discussionmentioning
confidence: 69%
“…This study showed with gestational age lower than 36 weeks, actinobacteria prevalence was significantly higher in females than males. and this was supported by Keskar et al (15) who revealed that Acinetobacter cases are more common in females, babies under 1500 g and under 30 weeks gestation than non-acinetobacter cases. Acinetobacter cases were less common among males, newborns with a birth weight of more than 1500 g, gestational ages of more than 30 weeks, and normal deliveries, compared to non-Acinetobacter cases.…”
Section: Discussionmentioning
confidence: 69%